Analisis Kepuasan Mutu Pelayanan PMB STISIP Widuri Menggunakan Metode Service Quality (SERVQUAL) - Insan Tri Bunawolo; Agus Budiyantara (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
This study examines student satisfaction with the New Student Admission (PMB) services at STISIP Widuri. In the competitive landscape of private higher education institutions (PTS), PMB is vital for attracting prospective students through effective marketing and high-quality services. The research, however, identifies that current levels of student satisfaction with PMB services at STISIP Widuri fall short of expectations. By applying the Service Quality framework, the study evaluates key service dimensions including reliability, responsiveness, and empathy. The results indicate that the services provided do not meet student expectations, leading to notable dissatisfaction. The study seeks to uncover the factors affecting student satisfaction and offers recommendations for enhancing service quality. The outcomes aim to make a significant impact on improving PMB services at STISIP Widuri, benefiting both academic and practical aspects. Ultimately, this research provides a foundation for improving higher education services, especially in the new student admission process. The recommendations are designed to strengthen the connection between the institution and its students, boost loyalty, and encourage positive word-of-mouth. Improving the quality of PMB services is crucial for achieving competitive advantage and enhancing the institution's reputation.